Influence of Gas from Long-Flame Coal Spontaneous Combustion on Gas Explosion Limit - Haitao Wang; Yongli Liu; Qiyuan Shan (International Journal of Chemical Engineering)
To investigate the impact of multiple combustible gases produced by long-flame coal spontaneous combustion on the gas explosion limit and to guide the reoperation of the coal mine goaf and fire area, the influence of gas generated by coal spontaneous combustion on gas explosion limit is investigated in this paper using a temperature-programmed device and a 20 L spherical explosion device. The results show that the volume fraction of CO produced during the spontaneous combustion of coal samples is 0.47%, followed by CH4 and C2H6, and C2H4 has the lowest content. Simultaneously, the coal spontaneous combustion is divided by 30°C, 80°C, and 170°C as the threshold, depending on the different gas characteristics. Organic C2H4 and C2H6 produced by coal spontaneous combustion have a greater impact on the CH4 explosion limit than inorganic CO. The lower and upper limits of CH4 explosion were reduced to 2.98% and 12.2%, respectively, by 0.8% C2H6. C2H4 and C2H6 explosion limits change dramatically when mixed with CH4. The CO and CH4 mixture explosion limit decreases first and then increases. C2H4 and C2H6 have a significant impact on the explosion pressure of mixed gas and the lower explosion limit of gas. The lower explosion limit falls from 5.1% to 4.3% as the explosion pressure rises from 0.25 MPa to 0.29 MPa.